Perbandingan Kinerja Web Server Terhadap Performa Integrasi Multi Basis Data - Dimas Pradana; Triawan Adi Cahyanto; Reni Umilasari; Hardian Oktavianto; Amalina Maryam Zakiyyah (BIOS : Jurnal Teknologi Informasi dan Rekayasa Komputer, 2022)
The research is focused for the purpose of analyzing the performance of which web server is able to receive more requests with a short connection time to support the performance of the integration application and can simulate the user with the jmeter application to test the web server. The performance test process is carried out using the benchmark test method using the Jmeter application by adjusting the input scenario and then analyzing the results based on the TIPHON standard. The results obtained from several variations of test parameters are known that the server's ability to send responses with the largest bytes is the apache web server, while the lowest error rate is nginx, while in terms of server network infrastructure, the apache web server is better because it can send a faster response. good and stable compared to nginx.Based on the test results above, it can be concluded that the apache web server has more effective results in web service performance against multi-database